Two steps forward, one step back: Renewable energy transitions in Bulgaria and Romania. (12th July 2018) - Davidescu, Simona; Hiteva, Ralitsa; Maltby, Tomas
Abstract : This article examines renewable energy policy in Bulgaria and Romania (2007–17) and the reasons behind the unexpected rapid growth in renewables followed by a policy reversal. While we find strong formal compliance with EU legislation regarding targets for renewable energy, an examination of institutional change and policy dismantling in both countries finds that this was not supported by a paradigmatic policy change or a transformation of the energy system. Veto players worked to dismantle renewable energy policy once targets were reached. We use insights from the intersection of socio‐technical systems and historical institutionalist literatures to explain policy dismantling in the energy sector. In doing so, we develop a socio‐technical account of renewable policy in Romania and Bulgaria. We show that this is related to the historically conditioned, path‐dependent processes of institutional change, where energy materiality shapes the parameters of political possibility and the costs of policy implementation.